The effect of giving lavender aromatherapy on primary menstrual pain (dysmenorrhea) - Khairun Nisa, Hanik (Institute of Accounting Research and Novation (IARN), 2023)
Dysmenorrhea (menstrual pain) is abdominal pain that comes from uterine cramps that occur during menstruation. Dysmenorrhea consists of primary and secondary dysmenorrhea. As many as 90% of adolescent women throughout the world experience problems during menstruation and more than 50% of menstruating women experience primary dysmenorrhea. Primary dysmenorrhea is menstrual pain that is not based on a pathological condition, while secondary dysmenorrhea is menstrual pain that is based on a pathological condition. The aim of this study was to analyze the effect of giving lavender aromatherapy on primary menstrual pain (dysmenorrhea) in Midwifery Study Program students at STIK Midwifery. This research method uses a pre-experimental one group pre and post test design. The research population was all 58 students of the STIK Bina Husada Midwifery Study Program, 20 total samples. The sampling technique uses purposive sampling. Data collection uses questionnaires and observation sheets. Analysis using the Spearman Rank correlation test (p=0.05). When giving 5 minutes of lavender aromatherapy there was no change in the respondent's pain scale, and when giving aromatherapy after 10 minutes there was a change so it can be concluded that there was an effect of giving lavender aromatherapy on primary menstrual pain (dysmenorrhea) in students of the STIK Bina Husada midwifery study program.